2021
DOI: 10.1136/postgradmedj-2020-139701
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic-induced hypokalaemia: an updated review

Abstract: Diuretic-induced hypokalaemia is a common and potentially life-threatening adverse drug reaction in clinical practice. Previous studies revealed a prevalence of 7%–56% of hypokalaemia in patients taking thiazide diuretics. The clinical manifestations of hypokalaemia due to diuretics are non-specific, varying from asymptomatic to fatal arrhythmia. Diagnosis of hypokalaemia is based on the level of serum potassium. ECG is useful in identifying the more severe consequences. A high dosage of diuretics and concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Alkalosis and hypokalemia also increased occurrences of EAD and long‐QT syndrome, which may be supported by following clinic reports. Diuretic‐induced hypokalemia was a common and potentially life‐threatening adverse drug reaction in clinical practice 54 . It was reported that among 31 patients suffering from heart disease with documented TdP due to quinidine, serum potassium concentrations were measured in 21 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkalosis and hypokalemia also increased occurrences of EAD and long‐QT syndrome, which may be supported by following clinic reports. Diuretic‐induced hypokalemia was a common and potentially life‐threatening adverse drug reaction in clinical practice 54 . It was reported that among 31 patients suffering from heart disease with documented TdP due to quinidine, serum potassium concentrations were measured in 21 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diuretic-induced hypokalemia was a common and potentially life-threatening adverse drug reaction in clinical practice. 54 It was reported that among 31 patients suffering from heart disease with documented TdP due to quinidine, serum potassium concentrations were measured in 21 patients. Five (24%) of 21 patients showed hypokalemia.…”
Section: Articlementioning
confidence: 99%
“…These results suggest that there may be a relation between potassium and phosphate, potentially mediated by FGF23. It has been shown that thiazide diuretics induce more hypokalemia than loop diuretics, despite the direct action of loop diuretics in Henle’s loop [ 37 ]. In the RS, thiazide diuretic users had lower serum potassium than nonusers.…”
Section: Discussionmentioning
confidence: 99%
“…16 Thiazide diuretic and loop diuretics are well-known causes of hypokalemia. 17 Hypomagnesemia is an important cause of hypokalemia. 18 Hypokalemia associated with magnesium deficiency is often refractory to treatment with potassium.…”
Section: Discussionmentioning
confidence: 99%
“…Both contain licorice and are known to cause hypokalemia attributable to pseudoaldosteronism 16 . Thiazide diuretic and loop diuretics are well‐known causes of hypokalemia 17 …”
Section: Discussionmentioning
confidence: 99%